Block Periodization 2: Fundamental Concepts & Training Design - Issurin, V. (Ultimate Athlete Concepts, 2008)
Previously titled Principles and Basics of Advanced Athletic Training, the books was renamed to more accurately capture the content of the book. The purpose of the second book by Dr. Issurin, published by Ultimate Athlete Concepts, is to provide basic knowledge on general training, summarize up-to-date information on the concepts of training effects and athletes' trainability, and to share new knowledge on training design and evaluation in the view of the Block Periodization system. The book contains materials and findings, which taken as a whole are devoted to reaching the aforementioned purposes. The basic terms, methods and principles of sport training, which clarify the comprehensive mechanism of physical fitness improvement, are presented in up-to-date interpretations. In particular, the effects produced by systematic training are a major focus of the author. An unequivocal understanding of training effects requires special elucidation which the author provides. Indeed, practical needs dictate making a distinction between short-term and long-term responses in athletes; such relatively new concepts as delayed and residual training effects have great importance both as a scientific background and practically, for the designing of training programs. Likewise, athlete trainability, meaning the ability to respond positively to training workloads, takes on paramount importance in sport science and athletic training. All these aspects are thoroughly considered with special attention given to the practical needs of coaches and athletes.